2009
DOI: 10.1158/1078-0432.ccr-08-2459
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Oncogenic Protein Kinase Cι Signaling in Lung Adenocarcinoma

Abstract: Purpose Atypical protein kinase Cι (PKCι) is an oncogene in non – small cell lung cancer (NSCLC). Here, we identify four functional gene targets of PKCι in lung adenocarcinoma (LAC), the most prominent form of NSCLC. Experimental Design Three independent public domain gene expression data sets were interrogated to identify genes coordinately expressed with PKCι in primary LAC tumors. Results were validated by QPCR in an independent set of primary LAC tumors. RNAi-mediated knockdown of PKCι and the target gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
4
38
0
2
Order By: Relevance
“…However, SOX2 is a LSCC-specific stem factor that is not highly expressed in LADC (Tatsumori et al, 2014; Yuan et al, 2010) suggesting that another transcription factor(s) may be targeted by PKCι in KRAS LADC oncospheres. In a meta-analysis, we identified four genes whose expression correlates with PKCι in multiple LADC gene expression datasets (Erdogan et al, 2009). Among these genes was ELF3 , an ETS family transcription factor implicated in lung epithelial stem cell maintenance (Oliver et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, SOX2 is a LSCC-specific stem factor that is not highly expressed in LADC (Tatsumori et al, 2014; Yuan et al, 2010) suggesting that another transcription factor(s) may be targeted by PKCι in KRAS LADC oncospheres. In a meta-analysis, we identified four genes whose expression correlates with PKCι in multiple LADC gene expression datasets (Erdogan et al, 2009). Among these genes was ELF3 , an ETS family transcription factor implicated in lung epithelial stem cell maintenance (Oliver et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In this process, MMP-10 acts as a critical effector of the PKC -Par6/Rac1 signaling axis that is required for anchorage-independent growth and invasion of NSCLC cells [313]. In PKC -dependent adenocarcinoma transformation, PKC induces four target genes, COPB2, ELF3, RFC4, and PLS1, whose expression has been correlated with PKC activity [314]. Therefore, overexpression of PKC is connected with poor survival in patients with NSCLC and can be used as a prognostic indicator [306].…”
Section: Small and Nonsmall Cell Lung Carcinomamentioning
confidence: 99%
“…Mining of public data has proved a useful approach in cancer research [40][41][42] . We found that the gene expression pattern of FST varied among the 149 clinical synovial samples The relative expression levels of FST mRNA and FST-correlated genes were determined in tissue samples from 149 patients with synovial sarcoma by meta-analysis; (Spearman r>0.6, P<0.001).…”
Section: Discussionmentioning
confidence: 99%